Porous silicon, preparation method thereof and porous silicon carbon negative electrode material
By forming metal M nanoparticles on p-type single crystal silicon wafers and etching and removing them, pure and uniform porous silicon is prepared, which solves the problems of complex processes and high cost in the existing methods and improves the performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202510014020.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-25
AI Technical Summary
The existing porous silicon preparation methods are complex in process, high in cost, low in efficiency, and difficult to form a uniform porous structure, which limits the performance improvement of lithium-ion batteries.
The metal M (such as Al) nanoparticles are formed on the cleaned p-type single crystal silicon wafer and etched in a mixed solution of HF and H2O2 to form pure, uniform porous silicon.
This method simplifies the preparation process of porous silicon, avoids the oxidation of silicon, forms an efficient lithium-ion de-embedding channel, and improves the energy storage and cycling performance of lithium-ion batteries.
Smart Images

Figure CN119890259A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to porous silicon and a preparation method thereof, and a porous silicon-carbon negative electrode material. Background Art
[0002] Porous silicon is a nanomaterial with a special structure. It has nanometer-sized pore walls and nanometer-sized open pores. In recent years, porous silicon has received extensive attention and in-depth research in the fields of life sciences (such as disease diagnosis and detection in vivo, photothermal therapy) and energy storage and conversion (such as lithium-ion batteries, solar cells) due to its biocompatibility, good luminescence properties, excellent photothermal conversion performance and huge energy density. Especially in the field of lithium batteries, porous silicon is particularly favored because of its large specific surface area, extremely thin pore walls and sufficiently large pore space, which can effectively inhibit electrode short circuits and shorten the transmission path of lithium ions, thereby improving the power density of the battery and extending the service life of the battery. At present, the commonly used negative electrode of lithium batteries is mainly graphite materials. The theoretical capacity of this type of material is only 372mAh / g. Its low theoretical specific capacity limits the overall improvement of lithium battery performance, so it is particularly important to develop new high-energy specific negative electrode materials.
[0003] Metallic silicon and lithium can form a silicon-lithium alloy (Li 4.4 Silicon is an ideal negative electrode material for lithium batteries, and its reserves are abundant and its sources are wide. However, silicon also has some disadvantages as a negative electrode material: (1) It is expensive and difficult to prepare. Usually, nano-silicon is prepared by high-energy ball milling or CVD, which requires expensive equipment, low yield and high cost; (2) The volume of metallic silicon expands during lithium storage, causing the electrode to pulverize and fall off, resulting in battery performance degradation; (3) Silicon is a semiconductor material with poor conductivity, which limits its rate performance.
[0004] The most common method to solve the above problems is to make silicon porous to form porous silicon or porous silicon metal, which can not only alleviate the volume expansion during lithium storage, but also the metal dispersed in the porous silicon can enhance its conductivity, and the rate performance is greatly improved. In the prior art, porous silicon is mainly prepared by anodization, thermal reduction, template method, chemical vapor deposition, etc.; for example, CN107032356B discloses a method for preparing porous nano-silicon, comprising the following steps: preparing crude magnesium disiloxane powder by chemical vapor deposition, then treating the crude magnesium disiloxane powder by hydrothermal method, and then purifying the product after hydrothermal treatment to obtain porous nano-silicon.
[0005] CN105529451A discloses a method for preparing porous elemental silicon, which includes using soft silicon as a raw material. The shape of the porous silicon is ellipsoidal. Compared with using solid silica balls, when soft silicon reacts with magnesium, magnesium can easily enter the interior of the porous silica, and heating by temperature zones is used to make the reaction more uniform. Compared with aerogel, the porous silicon structure is more intact and stable, and the wall thickness of the porous silicon can be maintained above 100 nm.
[0006] CN105399100A discloses a method for preparing nanoporous silicon using industrial silicon powder as raw material. The precursor Mg2Si / Mg composite material is prepared by alloying silicon powder and magnesium powder, and then dealloying is performed, and finally the obtained product is pickled, centrifuged, and dried to prepare nanoporous silicon.
[0007] CN110289402A discloses an electrode material of cross-linked carbon-coated mesoporous silicon particles, which is composed of porous silicon particles coated with carbon elements; its preparation method includes: firstly placing the crushed aluminum silicon alloy in a ball mill for liquid phase ball milling, then mixing and stirring the obtained aluminum silicon alloy powder and acid solution, then mixing and stirring the obtained mesoporous silicon particles, cationic surfactant and organic carbon source solution, and drying to obtain an intermediate product, and then calcining the intermediate product in a reducing atmosphere to obtain the electrode material of the cross-linked carbon-coated mesoporous silicon particles. In this technology, the outer layer of carbon coating is not complete during the carbon coating of the surface of the mesoporous silicon particles, resulting in a lot of exposed silicon on the surface of the material, consuming a large amount of active lithium in the process of forming the SEI film for the first time, forming a large irreversible capacity, and the first cycle coulomb efficiency of the obtained electrode material is low.
[0008] It can be seen that the existing methods for preparing porous silicon or porous silicon metal have the problem of many steps, complicated processes, high costs, and the generation of excess waste, which reduces its yield, and it is difficult to compound uniformly, resulting in difficulty in significantly improving its performance. These methods are often not suitable for large-scale production, which hinders the practical application of porous silicon negative electrode materials.
[0009] In summary, the existing methods for preparing porous silicon still have defects such as complex process, high cost, low efficiency, and difficulty in significantly improving performance. Therefore, there is an urgent need for a method for preparing nanoporous silicon that can solve the above problems. Summary of the invention
[0010] Based on the technical problems existing in the background technology, the present invention proposes porous silicon and a preparation method thereof, and a porous silicon-carbon negative electrode material.
[0011] The present invention provides a method for preparing porous silicon, comprising the following steps:
[0012] S1. Using a cleaned p-type single crystal silicon wafer as a substrate, using an oxide of metal M as an evaporation source, heating and evaporating the oxide of metal M in a reducing atmosphere to form metal M vapor, and condensing and depositing the metal M vapor on the substrate to form metal M nanoparticles, to obtain material I; the metal M is at least one of metals with an evaporation temperature ≤ 3000° C.;
[0013] S2. Immerse the material I in a mixed solution of HF and H2O2 to etch away the metal M nanoparticles to obtain porous silicon.
[0014] As the negative electrode material of lithium batteries, porous silicon must achieve a large specific capacity if lithium ions can be repeatedly deintercalated and intercalated between the pores of porous silicon, that is, the reversible deintercalation of lithium ions in porous silicon must be achieved. Only in this way can the continuous storage and conversion of chemical energy be achieved. Pure, deep, uniform, and open-pored porous silicon can provide a smooth deintercalation channel for lithium ions, preventing lithium ions from being bound and accumulated during the deintercalation process, resulting in irreversible capacity loss, thereby greatly improving the energy storage and cycle performance of lithium-ion batteries. The porous silicon is easily oxidized when the traditional method is used to prepare porous silicon, and an oxide layer is formed on the surface of the silicon, which affects the performance. The present invention first uses the oxide of metal M with an evaporation temperature of ≤3000°C as a metal source, forms metal M vapor by heating and evaporation, and then forms nano-metal M particles on the surface of the cleaned p-type single crystal silicon wafer by condensation, which covers the surface of the silicon as a chemically stable form to avoid oxidation of silicon; then HF and H2O2 system are used for etching. During the etching process, the oxide of metal M that may exist on the surface of the nano-metal M particles is removed under the action of acid, and the metal M combines with HF to form a complex, while releasing electrons, and then H2O2 is reduced by electrons. The metal M, HF and H2O2 system here is equivalent to forming a fuel cell. The accumulation of electrons causes the surface of the metal M to be negatively charged. At this time, the positively charged holes in the bulk Si are attracted by the negatively charged electrons on the aluminum surface to pass through the charge region back and forth and finally reach the interface between silicon and the etching solution, thereby participating in the dissolution of silicon and the formation of mesopores, and finally obtaining porous silicon.
[0015] Taking the metal M as Al as an example, the reaction principle of the porous silicon preparation of the present invention includes:
[0016] Al+6F - →[AlF6] 3- +3e -
[0017] H2O2+2H+2e - →2H2O
[0018] Si+4HF+4H + →SiF4+4H +
[0019] 4[AlF6]3-+3Si+12H + →3H2AlF6+4Fe+6HF
[0020] In the present invention, the purpose of cleaning the p-type single crystal silicon wafer is to remove impurities on the surface of the silicon wafer, and the cleaning method can adopt a conventional cleaning method in the art.
[0021] Preferably, in S1, the cleaning method of the p-type single crystal silicon wafer comprises: washing the p-type single crystal silicon wafer with ethanol, concentrated H2SO4, a mixed solution of concentrated H2SO4 and H2O2, HF acid buffer solution, a mixed solution of ammonia water and hydrogen peroxide, HF acid buffer solution, a mixed solution of hydrochloric acid and hydrogen peroxide, and HF acid buffer solution in sequence.
[0022] Preferably, the concentration of the concentrated H2SO4 is 11.5 mol / L to 18.4 mol / L;
[0023] Preferably, the mixed solution of concentrated H2SO4 and H2O2 is obtained by mixing H2O2 and concentrated H2SO4 at a volume ratio of H2O2 to concentrated H2SO4 of 1:4;
[0024] Preferably, the HF acid buffer solution is obtained by mixing deionized water, 50wt% HF solution and 30wt% hydrogen peroxide in a volume ratio of 60:3:2;
[0025] Preferably, the ammonia-hydrogen peroxide mixed solution is obtained by mixing deionized water, 25 wt% ammonia and 3 wt% hydrogen peroxide in a volume ratio of (1-10):1:1;
[0026] Preferably, the hydrochloric acid and hydrogen peroxide mixed solution is obtained by mixing deionized water, HCl, and 3 wt % hydrogen peroxide in a volume ratio of (1-10):1:1.
[0027] Preferably, the p-type single crystal silicon wafer is cleaned by immersion in ethanol for 10 to 20 minutes.
[0028] Preferably, the p-type single crystal silicon wafer is cleaned by immersion in concentrated H2SO4 for 40 to 50 minutes.
[0029] Preferably, the p-type single crystal silicon wafer is cleaned by soaking in a mixed solution of concentrated H2SO4 and H2O2 for 10 to 20 minutes.
[0030] Preferably, the p-type single crystal silicon wafer is cleaned with the HF acid buffer solution for 3 to 5 minutes each time.
[0031] Preferably, the p-type single crystal silicon wafer is cleaned with a mixed solution of ammonia and hydrogen peroxide in a water bath at 70 to 80° C. for 4 to 5 minutes.
[0032] Preferably, the p-type monocrystalline silicon wafer is cleaned with a mixed solution of hydrochloric acid and hydrogen peroxide in a water bath at 70 to 80° C. for 3 to 4 minutes.
[0033] In the present invention, the p-type single crystal silicon wafer is washed with ethanol, a mixed solution of concentrated H2SO4 and H2O2, HF acid buffer solution, a mixed solution of ammonia and hydrogen peroxide, HF acid buffer solution, a mixed solution of hydrochloric acid and hydrogen peroxide, and HF acid buffer solution, and then fully cleaned with deionized water.
[0034] Preferably, in S1, the temperature of heating evaporation is 600-3000°C, the holding time of heating evaporation is 1-3h, and the heating rate is 3-10°C / min. By controlling the temperature and time range of heating evaporation, the metal layer deposited on the silicon surface can be made more uniform, thereby improving the uniformity of forming porous silicon, which is beneficial to improving the energy storage and cycle performance of lithium-ion batteries.
[0035] Preferably, the reducing atmosphere is a mixed atmosphere of hydrogen and argon, wherein the volume proportion of hydrogen is 5-10%.
[0036] Preferably, the metal M is at least one of Al, Fe, Mg, Cu, Zn, Ni and Sn.
[0037] Preferably, in S1, the condensation time is 10 to 20 seconds.
[0038] Preferably, in S2, in the mixed solution of HF and H2O2, the concentration of H2O2 is 0.15-0.2M, and the concentration of HF is 5.3-21.2M. Preferably, in S2, the immersion etching time is 3-10min. By controlling the composition of the etching solution and the etching process parameters, holes with suitable pore size and structure can be formed on the surface of the wafer, which is beneficial to the reversible de-embedding of lithium ions, thereby further improving the energy storage and cycle performance of lithium-ion batteries.
[0039] In the present invention, the etching in S2 is performed in a dark environment.
[0040] The invention also provides porous silicon, which is prepared by the preparation method.
[0041] The present invention also provides a porous silicon-carbon negative electrode material, comprising the porous silicon and graphite, wherein the porous silicon accounts for 60-80% of the total mass of the negative electrode material, and the graphite accounts for 20-40% of the total mass of the negative electrode material.
[0042] Preferably, the preparation method of the porous silicon-carbon negative electrode material comprises: mixing the porous silicon and graphite and grinding them evenly, then placing the obtained mixture in a high-energy ball mill and ball milling at a rotation speed of 300 to 500 rpm for 0.5 to 1 h to obtain the obtained material.
[0043] The present invention also provides the use of the porous silicon or the porous silicon-carbon negative electrode material as a negative electrode material for a lithium ion battery.
[0044] The present invention also provides a lithium-ion battery, comprising: a positive electrode plate, a separator, a negative electrode plate and an electrolyte, wherein the negative electrode plate contains the porous silicon or the porous silicon-carbon negative electrode material.
[0045] The beneficial effects of the present invention are as follows:
[0046] The present invention first uses the oxide of metal M as a metal source, heats and evaporates to form metal M vapor, and then forms nano-metal M particles on the surface of a cleaned p-type single-crystal silicon wafer by condensation, which covers the surface of silicon as a chemically stable form to prevent silicon oxidation; then etched using an HF and H2O2 system, during which the metal oxide of M that may exist on the surface of the nano-metal M is removed under the action of acid, while the metal M and HF combine to form a complex - , releasing electrons at the same time, and then H2O2 is reduced by electrons. The metal M, HF and H2O2 system here is equivalent to forming a fuel cell. The accumulation of electrons causes the surface of the metal M to be negatively charged. At this time, the positively charged holes in the bulk Si are attracted by the negatively charged electrons on the surface of the metal M to pass back and forth through the charge zone and finally reach the interface between silicon and the etching solution, thereby participating in the dissolution of silicon and the formation of mesopores, and finally obtaining porous silicon. The method of the present invention is simple in process, and the oxidation of silicon can be avoided during the preparation of porous silicon. Pure and uniform porous silicon can be formed, so that the reversible deintercalation of lithium ions in porous silicon is faster and more stable, reducing the reversible capacity loss and improving the cycle performance of the battery. The porous silicon prepared by the present invention is assembled into a lithium-ion battery with a porous silicon-carbon negative electrode material formed after carbon doping, which has excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 The capacity and initial efficiency test results of a full battery assembled with the porous silicon-carbon negative electrode material in Example 1 of the present invention as the negative electrode material.
[0048] Figure 2 The test results of the cycle performance of a full battery assembled with the porous silicon-carbon negative electrode material in Example 1 of the present invention as the negative electrode material. DETAILED DESCRIPTION
[0049] The technical solution of the present invention is described in detail below through specific embodiments.
[0050] In the following examples, unless otherwise specified, all experimental reagents and raw materials involved are commercially available, and all reagents are analytically pure products.
[0051] In the following embodiments:
[0052] The concentration of concentrated H2SO4 is 18.4 mol / L;
[0053] The mixed solution of concentrated H2SO4 and H2O2 is obtained by mixing H2O2 and concentrated H2SO4 with a concentration of 18.4 mol / L in a volume ratio of 1:4;
[0054] The HF acid buffer solution is obtained by mixing deionized water, a 50 wt % HF solution, and a 30 wt % hydrogen peroxide solution in a volume ratio of 60:3:2;
[0055] The ammonia-hydrogen peroxide mixed solution is obtained by mixing deionized water, 25 wt % ammonia and 3 wt % hydrogen peroxide in a volume ratio of 10:1:1;
[0056] The hydrochloric acid hydrogen peroxide mixed solution is obtained by mixing deionized water, HCl, and 3 wt % hydrogen peroxide in a volume ratio of 10:1:1.
[0057] Example 1
[0058] Cleaning p-type monocrystalline silicon wafers:
[0059] 100 g of p-type single crystal (100) silicon wafer was placed in a beaker, first soaked in 1000 mL of ethanol for 15 min to remove organic compounds on the surface, and then cleaned with deionized water until no obvious foreign matter was found; then the wafer was soaked in 100 mL of concentrated H2SO4 for 45 min; then 30 wt% hydrogen peroxide (volume ratio hydrogen peroxide: concentrated H2SO4 = 1:1) was slowly added to the concentrated H2SO4, and the wafer was soaked for another 15 min; and the wafer was rinsed with deionized water several times; Wash with 100mL of HF acid buffer solution for 4 minutes, rinse several times with deionized water, and then soak in a mixed solution of ammonia and hydrogen peroxide at 75°C in a water bath for 4 minutes; rinse several times with deionized water; wash with 100mL of HF acid buffer solution for 4 minutes; rinse several times with deionized water; soak in a mixed solution of hydrochloric acid and hydrogen peroxide at 75°C in a water bath for 4 minutes; rinse several times with deionized water; wash with HF acid buffer solution for 4 minutes; wash several times with deionized water.
[0060] Preparation of porous silicon:
[0061] S1. The p-type single crystal (100) silicon wafer after cleaning is placed as a substrate in a vapor deposition device, and alumina is used as an evaporation source. The alumina is placed in a crucible, and in a reducing atmosphere (5% H2+95% Ar), a resistance wire or a laser heat source is used to heat and evaporate the alumina to form metal aluminum vapor under stirring. After the metal aluminum vapor condenses for 20 seconds, it is deposited on the substrate to form metal aluminum nanoparticles to obtain material I; the heating evaporation temperature is 2500°C, the heating evaporation holding time is 2h, and the heating rate is 5°C / min;
[0062] S2, the area is 1cm 2 Material I was immersed in a mixed solution of HF and H2O2 and etched for 5 minutes to remove metal aluminum nanoparticles to obtain porous silicon; in the mixed solution of HF and H2O2, the concentration of H2O2 was 0.18M, the concentration of HF was 21.2M, and the etching was carried out in a dark environment.
[0063] Preparation of porous silicon-carbon negative electrode material: Weigh porous silicon and graphite, mix and grind them evenly, then place the obtained mixture in a high-energy ball mill and ball mill it at a rotation speed of 400 rpm for 40 minutes.
[0064] Preparation of negative electrode sheet:
[0065] The binder, the conductive agent and the porous silicon-carbon negative electrode material are mixed in a weight ratio of 1:1:8, and then added to NMP (N-methylpyrrolidone) to prepare a slurry. The slurry is coated on the surface of the copper foil and then dried to obtain a negative electrode sheet.
[0066] Example 2
[0067] The difference between Example 2 and Example 1 is that the process parameters for preparing porous silicon are different, which are as follows:
[0068] Preparation of porous silicon:
[0069] S1. The p-type single crystal (100) silicon wafer after cleaning is placed as a substrate in a vapor deposition device, and alumina is used as an evaporation source. The alumina is placed in a crucible, and in a reducing atmosphere (5% H2+95% Ar), a resistance wire or a laser heat source is used to heat and evaporate the alumina to form metal aluminum vapor under stirring. After the metal aluminum vapor condenses for 20 seconds, it is deposited on the substrate to form metal aluminum nanoparticles to obtain material I; the heating evaporation temperature is 2500°C, the heating evaporation holding time is 2h, and the heating rate is 5°C / min;
[0070] S2, the area is 1cm 2Material I was immersed in a mixed solution of HF and H2O2 and etched for 10 minutes to remove metal aluminum nanoparticles to obtain porous silicon; in the mixed solution of HF and H2O2, the concentration of H2O2 was 0.18M, the concentration of HF was 5.3M, and the etching was carried out in a dark environment.
[0071] Example 3
[0072] Preparation of porous silicon:
[0073] S1. The cleaned p-type single crystal (100) silicon wafer is placed as a substrate in a vapor deposition device, and magnesium oxide is used as an evaporation source. The magnesium oxide is placed in a crucible, and in a reducing atmosphere (5% H2+95% Ar), the magnesium oxide is heated and evaporated by a resistance wire or a laser heat source under stirring to form metal magnesium vapor. After the metal magnesium vapor is condensed for 20 seconds, it is deposited on the substrate to form metal magnesium nanoparticles to obtain material I; the heating evaporation temperature is 1200°C, the heating evaporation holding time is 2 hours, and the heating rate is 5°C / min;
[0074] S2, the area is 1cm 2 Material I was immersed in a mixed solution of HF and H2O2 and etched for 5 minutes to remove the metal magnesium nanoparticles to obtain porous silicon; in the mixed solution of HF and H2O2, the concentration of H2O2 was 0.18M, the concentration of HF was 21.2M, and the etching was carried out in a dark environment.
[0075] Test example
[0076] The electrochemical performance of the material was evaluated using a standard CR2025 button cell. In a glove box filled with Ar (the contents of H2O and O2 were both less than 0.1ppm), the porous silicon-carbon negative electrode material in Example 1 was used as the negative electrode material, lithium iron phosphate was used as the positive electrode material, and Celgard 2500 was used as the separator to assemble a full battery. The preparation method of the electrolyte comprises: dissolving LiPF6 in EC:EMC=3:7 to obtain a solution with a concentration of 1.0M, and then adding 1.0wt% VC to obtain. The assembled battery was left to stand for 24h for subsequent charge and discharge tests. For test results, see Figure 1 and Figure 2 , the N / P ratio was controlled at 1.1, the first coulombic efficiency of the battery was 89%, and after 100 cycles, the capacity retention rate was 96.3%.
[0077] The porous silicon-carbon negative electrode materials of Examples 2 to 3 were performance tested with reference to the above test conditions, and the test results are as follows: the first coulombic efficiency of the battery of Example 2 is 89.3%, and after 100 cycles, the capacity retention rate is 98.2%; the first coulombic efficiency of the battery of Example 3 is 88.9%, and after 100 cycles, the capacity retention rate is 98.6%.
[0078] The present invention has no special requirements for the assembly process of the battery, and the battery can be assembled using methods known in the art. The present invention will not be described in detail here, and those skilled in the art should not interpret this as a limitation of the present invention.
[0079] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing porous silicon, characterized in that: The following steps are involved: S1. Using a cleaned p-type single crystal silicon wafer as a substrate and an oxide of metal M as an evaporation source, heating and evaporating the oxide of metal M in a reducing atmosphere to form metal M vapor, wherein the metal M vapor is condensed and deposited on the substrate to form metal M nanoparticles, thereby obtaining material I; the metal M is at least one of metals having an evaporation temperature of ≤3000° C.; S2. Immerse the material I in a mixed solution of HF and H2O2 to etch away the metal M nanoparticles to obtain porous silicon.
2. The method for preparing porous silicon according to claim 1, characterized in that: In S1, the temperature of heating evaporation is 600-3000°C, the insulation time of heating evaporation is 1-3h, and the heating rate is 3-10°C / min.
3. The method for preparing porous silicon according to claim 1, characterized in that: In S1, the metal M is at least one of Al, Fe, Mg, Cu, Zn, Ni, and Sn.
4. The method for preparing porous silicon according to claim 1, characterized in that: In S2, in the mixed solution of HF and H2O2, the concentration of H2O2 is 0.15-0.2M, and the concentration of HF is 5.3-21.2M.
5. The method for preparing porous silicon according to claim 1, characterized in that: In S2, the immersion etching time is 3 to 10 minutes.
6. A porous silicon, characterized in that: The method is prepared according to any one of claims 1 to 5.
7. A porous silicon-carbon negative electrode material, characterized in that: It comprises the porous silicon and graphite as claimed in claim 6, wherein the porous silicon accounts for 60-80% of the total mass of the negative electrode material, and the graphite accounts for 20-40% of the total mass of the negative electrode material.
8. Use of the porous silicon according to claim 6 or the porous silicon-carbon negative electrode material according to claim 7 as a negative electrode material for lithium-ion batteries.
9. A lithium ion battery, characterized in that: include: A positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet contains the porous silicon according to claim 6 or the porous silicon-carbon negative electrode material according to claim 7.
Citation Information
Patent Citations
Preparation method and application for metal modified porous silicon powder
CN105680008A
Preparation method of lithium ion battery nanoporous silicon negative electrode material
CN110350181A
Method for preparing boron-doped nano-metal / porous silicon-carbon composite negative electrode based on cut silicon wastes
CN111799460A
Non-filled carbon-coated metal-modified porous silicon negative electrode material and preparation method thereof
CN115602818A
Metal nanoparticle loaded honeycomb-like porous silicon film and thermopile chip thereof
CN116828957A